Analisis Kuantitas dan Kualitas Air dalam Pengembangan Pemanfaatan Sumber Daya Air Sungai di Kawasan Hutan Lindung Sungai Wain - Sukristiyono Sukristiyono; Ris Hadi Purwanto; Hatma Suryatmojo; Sumardi Sumardi (Jurnal Wilayah dan Lingkungan, 2021)
The increase in population every year and the relatively high economic growth in Balikpapan City have had a negative impact on the environment related to the use of water resources. Human activities in the protected forest areas have caused degradation and deforestation of protected forest areas resulting in the three rivers currently unable to meet water needs during the dry season. This study aims to assess the feasibility of river water in the Sungai Wain protected forest in terms of quantity and quality as an effort to provide alternative sources of raw water for the development of urban facilities.  Analysis of water samples was carried out at the Regional Health Laboratory, Balikpapan City Health Office. The results showed that the Wain river water discharge was 0.334 m3/s, the Bugis river was 0.258 m3/s, while the Sengkuang river was 0.032 m3/s. The physical quality of water from the three rivers meets the standards of environmental health quality standards. The chemical quality of water indicates the pH and iron parameters do not meet environmental health quality standards. The biological quality of water indicates the total number of coliform in Bugis river is 920; Wain River 350, and Sengkuang River 350. The results of analysis of Escherecia coli bacteria showed that the content of Escherecia coli bacteria exceeded the maximum allowed amount.  The results of this research can be taken into consideration for the Balikpapan city government to plan the development of river water utilization in the Sungai Wain protected forest area.